Etude électrochimique et théorique de l’inhibition de la corrosion aqueuse de l’acier doux par quelques porphyrines et leurs complexes métalliques - MERAGHNI Messaoud (Universty Of El-oued جامعة الوادي, 2025)
The influence of porphyrin-derived compounds, such as 5,10,15,20- tetraphenylporphyrin (TPPH2), 5,10,15,20-tetra-p-tolylporphyrin (TPPH2(p-Me)), and 1,1',1'',1'''-(porphyrin-5,10,15,20-tetrayltetrakis(benzene-4,1-diyl))tetrakis(ethan- 1-one) (TAcPPH2), on the aqueous corrosion of mild steel XC52 in 0.5M sulfuric acid has been examined. This study utilized electrochemical impedance spectroscopy and potentiodynamic polarization. Parameters considered included concentration and temperature. The electrochemical results showed that these three inhibitors exhibit a mixed nature and are highly effective in protecting XC52 steel against corrosion in the presence of a 0.5M H2SO4 solution. Notably, TAcPPH2 proved to be the most effective inhibitor, and the protective effect was directly linked to the electron- donating nature of the substituent. The mechanisms of action of these inhibitors were examined through thermodynamic studies, and calculations of parameters such as ΔG°ads, Ea, ΔHa, and ΔSa confirmed that all inhibitors are effectively adsorbed through a physisorption process. This adsorption was found to be spontaneous and followed the Langmuir adsorption isotherm. Additionally, a surface analysis conducted via UV-Visible confirmed the electrochemical and thermodynamic results. Quantum calculations performed using DFT and MDS also corroborated the experimental findings تم دراسة تأثير مركبات مشتقة من البورفيرين، مثل (TPPH2) و (TPPH2(p-Me)) و (TAcPPH2) ، على عملية تآكل الفولاذ الكربوني XC52 في وسط حمضي من حمض الكبريت بتركيز 0.5 مولار. تم استخدام تقنيات مختلفة في هذه الدراسة، بما في ذلك قياسات الاستقطاب والممانعة الكهروكيميائية. كما تم دراسة تأثير تغير التركيز ودرجة الحرارة على هذه العملية. أظهرت النتائج التجريبية أن هذه المركبات تعمل كمثبطات للتآكل بطريقة مختلطة، و أنها فعالة بشكل كبير في تقليل معدل تآكل الفولاذ في وسط حمض الكبريتيك. ومن بين هذه المركبات، تبين أن (TAcPPH2) هو الأكثر فعالية. كما لوحظ أن فعالية هذه المثبطات ترتبط بشكل مباشر بقدرتها على التبرع بالإلكترونات. تم دراسة آلية تثبيط التآكل من خلال دراسات الديناميكا الحرارية. وقد أظهرت حسابات الطاقة الحرة لامتصاص (ΔG°ads) وطاقة التنشيط (Ea) وأنثالبي (ΔHa) وإنتروبي (ΔSa) الامتصاص أن هذه المركبات تمتص على سطح الفولاذ بطريقة فيزيائية. كما أن عملية الامتصاص هذه هي عملية تلقائية وتتبع نموذج امتزاز لانجموير. تم تأكيد النتائج التجريبية والحسابات الديناميكية الحرارية من خلال تحليل سطح الفولاذ باستخدام تقنية الأشعة فوق البنفسجية والمرئية (UV-Visible). كما تم إجراء حسابات كمية باستخدام نظريتي كثافة الحالة (DFT) وديناميكا الجزيئات (MDs) لدعم النتائج التجريبية."
أطروحة دكتوراه تخصص: هندسة كيميائية في العلوم التكنولوجيا
Keywords: corrosion; electrochemistry; Tafel; electrochemical impedance spectroscopy.; الاستقطاب، الممانعة الكهروكيميائية، الديناميكا الحرارية، DFT، و MDS.